Involvement of Gut Microbiota in the Development of Psoriasis Vulgaris - Sun, Chaonan; Chen, Ling; Yang, Huan; Sun, Hongjiang; Xie, Zhen; Zhao, Bei; Jiang, Xuemei; Qin, Bi; Shen, Zhu (Frontiers in Nutrition, 2021)
Objectives Psoriasis is a common chronic recurrent dermatitis. Accumulating observations show gut microbiota dysbiosis in psoriasis. We intend to further investigate the relationship between intestinal microbiota and psoriasis development. Design We first performed an epidemiological investigation on differences of gastrointestinal discomfort symptoms between psoriatic patients and general population. Then variation of gut microbiota in psoriatic patients (un)treated with acitretin plus NB-UVB was analyzed by 16S rRNA sequencing. We last compared recovery status and vital cytokines (lesion and intestine) of mouse psoriasiform models, which were transplanted with fecal microbiota from psoriatic patients or healthy controls. Results (1) 85.5% of psoriatic patients versus 58.1% of healthy controls presented with at least one gastrointestinal symptom. The prevalence of investigated symptoms (e.g. abdominal distension, constipation) were significantly higher in patients, compared with controls (p<0.05). Passing flatus and constipation were significantly correlated with psoriasis (p<0.05 in both cases). (2) The abundance of Ruminococcaceae family, Coprococcus_1 genus and Blautia genus were decreased with psoriasis improvement (p<0.05, respectively), which had been demonstrated significantly increased in psoriasis. (3) Mice receiving psoriatic microbes transplantation showed delayed recovery of psoriasiform dermatitis and less reduction of IL-17A, than those receiving healthy microbiota or blank control (p<0.05 and p<0.01, respectively). Conclusion Multiple evidence we provided here preliminarily demonstrate the involvement of gut microbiota in the different degree of psoriasis activity. The strategy based on overall microbial communities is expected to be a promising supplementary for long-term management of psoriasis.